ANALYSIS OF GULLY DIMENSIONS AND SEDIMENT TEXTURE FROM SOUTHEAST AUSTRALIA FOR CATCHMENT SEDIMENT BUDGETING - Rustomji P. (My University, 2006)
Catchment scale sediment budgeting models are increasingly being used to target remediation works aimed at controlling erosion and improving water quality. Gully erosion is often a major sediment source and needs to be accounted for in such models in a manner consistent with the scale of analysis and available data. Using 130 measurements of gully cross-sectional area and 45 measurements of gully wall sediment texture, the variability in gully dimensions and particle size distribution for the Lake Burragorang catchment in Australia is examined. The distribution of gully cross-sectional area measurements is log-normally distributed and modelling indicates a representative value of 23 m2 be used in catchment sediment budgeting applications. The proportion of gully eroded sediment contributing to the bedload budget (defined as particles > 63 μm diameter) of a river link is approximately half, though may be higher in igneous landscapes. A continental scale spatially distributed subsoil texture dataset provided limited capacity to predict the finer scale spatial variation in the proportion of sediment contributing to bedload from gully erosion within the Lake Burragorang catchment. Crown Copyright © 2006.
Keywords: BEDLOAD; CATCHMENT; GULLY; SEDIMENT BUDGET